Isoacids supplementation improves growth performance and feed fiber digestibility associated with ruminal bacterial community in yaks - Jiang, Fei; Gao, Yanhua; Peng, Zhongli; Ma, Xiulian; You, Yinjie; Hu, Zhibin; He, Anxiang; Liao, Yupeng (Frontiers in Microbiology, 2023)
This study was conducted to assess the effect of mixed isoacid (MI) supplementation on fermentation characteristics, nutrient apparent digestibility, growth performance, and rumen bacterial community in yaks. A 72-h in vitro fermentation experiment was performed on an ANKOM RF gas production system. MI was added to five treatments at doses of 0, 0.1%, 0.2%, 0.3%, 0.4%, and 0.5% on the dry matter (DM) basis of substrates using a total of 26 bottles (4 bottles per treatment and 2 bottles as the blank). Cumulative gas production was measured at 4, 8, 16, 24, 36, 48 and 72 h. Fermentation characteristics including pH, the concentration of volatile fatty acids (VFAs), ammonia nitrogen (NH3-N), microbial proteins (MCP), and the disappearance rate of dry matter (DMD), neutral detergent fiber (NDFD), and acid detergent fiber (ADFD) were measured after a 72-h in vitro fermentation to determine an optimal MI dose. Supplementation with 0.3% MI achieved the greatest propionate and butyrate content, NDFD and ADFD compared with other groups (P< 0.05). Therefore, 0.3% was used for the animal experiment. Fourteen Maiwa male yaks (180-220 kg, 3-4 years old of age) were randomly assigned to the control group (without MI, n=7) and the supplemented MI group (n=7, supplemented with 0.3% MI on DM basis) for the 85-d animal experiment. Growth performance, nutrient apparent digestibility, rumen fermentation parameters, and rumen bacterial diversity were measured. Supplementation with 0.3% MI significantly increased the apparent digestibility of NDF and ADF (P<0.05), and the average daily weight gain of yaks (P <0.05) without affecting the ruminal concentration of NH3-N, MCP, and VFAs. 0.3% MI induced rumen bacteria to form significantly different communities when compared to the control group (P<0.05). g__norank_f__Bacteroidales_BS11_gut_group, g__norank_f__Muribaculaceae, , g__Veillonellaceae_UCG-001, g__Ruminococcus-_gauvreauii_group, g__norank_f__norank_o__RF39 and g__Flexilinea were identified as the biomarker taxa in responding to supplementation with 0.3% MI. Meanwhile, the abundance of g__Flexilinea and g__norank_f__norank_o__RF39 were significantly positively correlated with the NDF digestibility (P<0.05). In conclusion, supplementation with 0.3% MI improved the in vitro rumen fermentation characteristics, feed fiber digestibility, and growth performance in yaks, which was positively correlated with the abundance of g__Flexilinea and g__norank_f__norank_o__RF39.